Administrators’ Supervisory Skills that Influence the World Class Standard Outcomes of Secondary Schools - Thongsri, Phattanapong; Bulpakdi, Buntarika; Sudrung, Jurairat (An Online Journal of Education, 2023)
The objectives of this research were: 1) to study the level of supervision skills of school administrators who have been awarded the world-class standard school award at the secondary level; 2) to study the level of performance of the outcomes of schools that have been awarded the world-class standard school award for secondary education, and 3) to study the supervision skills of school administrators that affect the outcomes of world-class standard secondary schools. The population used in the research was among 280 schools that received the quality award from the Office of the Basic Education Commission for secondary education. The informants are five teachers from each school who perform the duties of school supervisors, namely curriculum, grade level, personnel, policy and planning, and financial management, totaling 810 informants. Research instruments include a 5-level rating scale questionnaire, data analysis using frequency, percentage, mean, standard deviation, correlation coefficient analysis, and enter multiple regression analysis. The research results showed that 1) executives’ overall level of supervision skills averaged 4.04 at the high level. 2) The performance level of world class standard school outcomes averages 4.89 at the highest level. 3) two skills in executive supervision affect the outcome of world class standard school: personnel management skills and assessment skills.